2003
DOI: 10.1614/0890-037x(2003)017[0256:cbortp]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Cabbage (Brassica oleracea) Response to Pendimethalin Applied Posttransplant1

Abstract: Field and greenhouse studies were conducted from 1997 to 2001 to determine cabbage response to posttransplant applications of pendimethalin (0.56 to 2.24 kg ai/ha). Differential variety response was minimal, and applications greater than 0.56 kg caused severe and persistent crop injury and reduced head number and yield in ‘Azan’, ‘Storage 4’, ‘Super Elite’, and ‘Super Red 90’. Pendimethalin (1.7 kg) applied posttransplant reduced cabbage yield weights 23, 30, and 87% with bare root, large, and small transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Dinitroaniline herbicides injure plants by binding to tubulin molecules, which ultimately leads to an inhibition of cell mitosis (Appleby and Valverde 1989). Information on absorption and translocation within plants is less clearly defined; however, direct entry into plant tissue is considered limited, and unless the dinitroaniline herbicide enters meristematic tissues, the herbicide will have little effect on plant growth (Miller et al 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Dinitroaniline herbicides injure plants by binding to tubulin molecules, which ultimately leads to an inhibition of cell mitosis (Appleby and Valverde 1989). Information on absorption and translocation within plants is less clearly defined; however, direct entry into plant tissue is considered limited, and unless the dinitroaniline herbicide enters meristematic tissues, the herbicide will have little effect on plant growth (Miller et al 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Larger transplants or a longer acclimation period may have reduced herbicide phytotoxicity. Miller et al (2003) observed greater yields (34 kg ha À1 x 1000 À1 ) of large transplant (5 to 6 true leaf) cabbage (Brassica oleracea L.) compared to small transplants (4 to 5 true leaf) (5 kg ha À1 x 1000 À1 ) in response to PRE applications of pendimethalin at 1.7 kg ai ha À1 .…”
Section: Resultsmentioning
confidence: 93%
“…Derr and Salihu (1996) reported that a decrease in efficacy of several preemergence herbicides on redtip photinia (Photinia •fraserii), 'Tradition' azalea (Rhododendron obtusum), abelia (Abelia grandiflora • A. Schumannii), and 'Helleri' japanese holly (Ilex crenata) may have been caused by an increase in plant size. Miller et al (2003) observed greater yields (34 kgÁha -1 ) of large transplant (five to six true leaves) cabbage (Brassica oleracea var. capitata) compared with small transplants (four to five true leaves) (5 kgÁha -1 ) in response to preemergence applications of pendimethalin at 1.7 kgÁha -1 .…”
Section: Resultsmentioning
confidence: 95%